A New Leaf Based on a Story by Jack Ritchie - May, Elaine; Rescher, Gayne; Matthau, Walter; Redfield, William (The Masters of Cinema Series, 2015)
One of America's greatest comic legends, Elaine May, made her debut as writer and director in the wonderful "A New Leaf". Unanimously acclaimed from the start, but unavailable for many years, it now stands as a classic alongside "Harold and Maude", "Bananas" and "M*A*S*H*" as a key film in the new direction of American screen comedy in the 1970s. The great Walter Matthau stars as Henry, a once-rich playboy who has obliviously spent his entire inheritance. Desperate to marry into further financial support, he meets Henrietta (Elaine May), a shy, awkward, though independently wealthy botany professor. What follows is a giddy tale of dubious legal advice, ruthless skulduggery and ferns. [Cover]